HONEY-MUMFORD LEARNING STYLE: REVIEW OF MATHEMATICAL COMMUNICATION FOR ELEMENTARY SCHOOL STUDENTS IN PROBLEM SOLVING - Awal Nur Kholifatur Rosyidah; Umar Umar; Vivi Rachmatul Hidayati; Mohammad Archi Maulyda; Lalu Wira Zain Amrullah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Mathematical communication skills are very important for students, especially for elementary school students. Students' communication skills in each student are always different, as are different learning styles for each student. The purpose of this study is to describe the mathematical communication process carried out by students in each type of learning style they have. The learning styles referred to refer to Honey-Mumford, namely; (1) Theoretical; (2) Pragmatic; (3) Activist; and (4) Reflective. The research was carried out at SDN 44 Ampenan, with the subjects being all of the fifth-grade students, totaling 39 students. Data collection was carried out by providing 2 instruments, namely a learning style questionnaire and math problems followed by semi-structured interviews to students who had finished. The results showed that the number of students with theoretical learning styles was the highest and students with active learning styles were the least. The results of the study also show that there are differences in mathematical communication in each learning style, but mathematical communication errors made by all types of learning styles are errors in writing formulas and conclusion sentences